Selective oxidation of primary and secondary alcohols to corresponding aldehydes and ketones using a mild oxidant, Isoquinoliniumchlorochromate. (2021) - MohanKumar, R.; Arthanareeswari, M.; Ganesh, M.R.
Abstract: Isoquinoliniumchlorochromate (IQCC) is a mild oxidant for effective conversion of primary and secondary alcohols to corresponding aldehydes and ketones.